Case report: A case report and literature review about Pathological transformation of lung adenosquamous cell carcinoma - Ge-ge, Liang; Cuicui, Geng; Leiqiang, Li; Yongcang, Tian; Jiangang, Ma; Yiwen, Ou; Li-zhe, Sun (Frontiers in Oncology, 2022)
Background: lung adenosquamous carcinoma is a relatively rare pathological type in lung cancer. The incidence of gene mutation is lower than that of lung adenocarcinoma. However, the cases of pathological transformation after targeted treatment of EGFR gene mutation are more rare. Case introduction: a 55 year old female was diagnosed with lung cancer and underwent surgical treatment.The pathology suggested adenosquamous cell carcinoma. Genetic test was EGFR-L858R. After surgery, she was treated with gefitinib targeted therapy. After 2 years of surgery, she developed brain metastasis. surgery was performed again. The pathology suggested squamous cell carcinoma. She continued to take gefitinib targeted therapy orally. After one month later since brain metastasis, she was found to have heart cavity metastasis and surgery was performed for the third time. Besides, the pathology suggested adenosquamous cell carcinoma. Genetic test was EGFR-p E746_ A750del, T790M (-), and we replaced with the second-generation EGFR-TKI afatinib targeted therapy. Up to now, no recurrence or metastasis has been found. Conclusion: we now report a rare case of lung adenosquamous carcinoma with pathological transformation during targeted therapy, which is intended to provide therapeutic ideas for the treatment of lung adenosquamous carcinoma in clinical practice. In addition, we reviewed previously reported tumor heterogeneity in the literature.